1995
DOI: 10.1159/000188738
|View full text |Cite
|
Sign up to set email alerts
|

Role of Peritoneal Loss of Albumin in the Hypoalbuminemia of Continuous Ambulatory Peritoneal Dialysis Patients: Relationship to Peritoneal Transport of Solutes

Abstract: The effects of peritoneal albumin loss and the consequences of heterogeneous peritoneal solute transport on serum albumin levels were investigated in 25 adult patients on standard continuous ambulatory peritoneal dialysis (0-58 months). The patients were divided into three groups according to their albumin concentrations (g/l/1.73 m2) in 8-hour overnight effluents: group 1 ( < 0.6, n = 5), group 2 (0.6- 1.1; n = 14), and group 3 ( > l.l; n = 6). Significant differences (mean ± SD) were observed in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 10 publications
(20 reference statements)
2
8
0
Order By: Relevance
“…In the present study, we found that serum prealbumin level is approximately 70 mg/L higher in PD than HD, while serum albumin is approximately 2.8 g/L lower in PD, which was paralleled with previous studies 29–31 . The reason for the decrease in serum albumin in PD is probably due to the peritoneal loss of albumin; 32,33 however, the reason for the increase in prealbumin in PD is unknown. It has been hypothesized that serum prealbumin is increased as a result of the stimulation of hepatic synthesis by the large loss of albumin and/or the resultant hypoalbuminemia hepatic synthesis or reduced systemic catabolism 31,34–36 …”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we found that serum prealbumin level is approximately 70 mg/L higher in PD than HD, while serum albumin is approximately 2.8 g/L lower in PD, which was paralleled with previous studies 29–31 . The reason for the decrease in serum albumin in PD is probably due to the peritoneal loss of albumin; 32,33 however, the reason for the increase in prealbumin in PD is unknown. It has been hypothesized that serum prealbumin is increased as a result of the stimulation of hepatic synthesis by the large loss of albumin and/or the resultant hypoalbuminemia hepatic synthesis or reduced systemic catabolism 31,34–36 …”
Section: Discussionsupporting
confidence: 90%
“…Nolph et al (33) and Kang et al (27) demonstrated that high peritoneal permeability was associated with a reduced normalized protein catabolic rate and composite nutritional index, but these associations were not confirmed by the CANUSA study (7). The greater prevalence of hypoalbuminemia in high transporters may also arise from hemodilution secondary to suboptimal ultrafiltration (34) or from excessive peritoneal protein losses (28). Alternatively, hypoalbuminemia in high transporters may reflect a greater incidence of underlying chronic inflammation (12,35), although other studies have not observed a significant correlation between D:P Cr 4 h and various inflammatory markers, such as C-reactive protein (4,36).…”
Section: Discussionmentioning
confidence: 99%
“…HTs have lower levels of plasma albumin (3-5, 8, 10, 20, 26-28). Serum albumin is generally found to be negatively correlated to peritoneal loss of albumin (3,5,8,22,(29)(30)(31)(32) and both are correlated to transport status (3,8,10,11,26,31,33). Peritoneal protein loss is substantial in HTs (8-13 g/day) compared to LTs (5-6 g/day), and is clearly in the nephrotic range.…”
Section: Loss Of Albuminmentioning
confidence: 99%